Desenvolvimento e uso de tecnologia leve para prevenção do câncer de boca - SILVA, Amanda Thayse Silva e (2023)
: The oral cancer presents itself as a prevalent public health problem with impacting morbidity rates. Early detection is one of the best strategies to face it, so health education has a prominent place in the care of this disease. Following this concept, this study proposed the creation of light technology based on the principles of popular health education that aims to disseminate previous knowledge about the disease, contributing to its prevention. The light technology developed was in the form of a canvas banner containing adapted language to popular education, addressing the theme of self-examination of the mouth, signs and risk factors containing images, guaranteeing health literacy for the population. The material presented good performance of use and proved to be effective in verbal communication, in conversation circles and community interaction. Therefore, the use of light technology seems to be effective in literacy about oral cancer for the population, and it can be applied in adverse conditions and in the Amazonian communities, allowing interaction between the surgeon-dentists and the public for clarifications about the pathology.